Anisotropic Lithium ion Migration in LiFePO4 - Park, S. B.; Park, C. K.; Hwang, J. T.; Cho, W. I.; Jang, H. (KOREAN INST METALS MATERIALS, 2011)
An anisotropic behavior of lithium ion migration in LiFePO4 is investigated using the cathode particles after chemical delithiation. A phase contrast of a LiFePO4 particle validating the directional property is also found. It suggests that the lithium ion migration path is limited to the [010] direction and the phase boundary between LiFePO4 and FePO4 is perpendicular [010]. The symmetric phase boundary inside the LiFePO4 particle is contrary to the non-directional core-shell model reported by others. The molecular dynamics simulation confirms the crystallographic direction with the lowest energy for lithium ion migration.